Tam protez kullanan hastalarda demografik faktörler, protez yaşı ve çiğneme kuvvetinin yaşam kalitesi ve hasta memnuniyeti üzerine etkisinin incelenmesi - Ali Yabul; Cagatay Dayan; Emre Mumcu; Hakan Bilhan; Necat Tuncer; Onur Geckili (Cumhuriyet University, 2012)
Objectives: In our country, the majority of people over age 65 is determined using maxillary and mandibular complete dentures; for this reason, the investigation of the effect of this treatment type on patient satisfaction and life quality and the bite forces is important. The aim of this retrospective study was to analyze the effect of age, gender, bite force and age of the prosthesis on quality of life and patient satisfaction of patients using complete dentures for at least 3 years. Materials and Methods: 50 edentulous patients using maxillary and mandibular complete dentures for no less than 3 years were included in this study. Bite forces were measured in all patients, and patients were asked to complete OHIP-14 forms for detecting life quality and Visual Analog Scale (VAS) forms for detecting patient satisfaction. Results: According to the statistical outputs of the study, no statistically significance was found between the patient age, gender and VAS and OHIP scores (p>0.05). Statistically significant relationship was found between denture age and VAS speech scores in positive way, at a level of 30.8%, and denture age and OHIP functional disability scores in a negative way, at a level of 32.2%. Statistically significant relationship was found between bite force and VAS speech scores of the patients in positive way, at a level of 29.6%, whereas a statistically significant relationship was not found between OHIP scores(p>0.05) and bite forces. In addition, bite forces of the male patients were significantly higher than female patients (p<0.05). Conclusions: In maxillary and mandibular complete denture wearers, demographic factors like age and gender do not seem to effect patient satisfaction and life quality; however age of the prosthesis and bite forces affect speech satisfaction of the patients. ÖZET Amaç: Ülkemizde 65 yaş üstü bireylerin çoğunun alt üst tam protez kullandığı saptanmış olduğu için, bu tedavi şeklinin hasta memnuniyeti ve yaşam kalitesine olan etkisi ve ısırma kuvvetlerinin araştırılması önem taşımaktadır. Bu retrospektif çalışmanın amacı, en az 3 senedir tam protez kullanan hastalarda yaş, cinsiyet, ısırma kuvveti ve protez yaşının yaşam kalitesi ve hasta memnuniyeti üzerine etkisinin incelenmesidir. Gereç ve Yöntem: En az 3 yıldır protezlerini kullanmakta olan 50 dişsiz hasta bu çalışmaya dahil edilmiştir. Tüm hastaların ısırma kuvvetleri ölçülmüş, ve hastalara hasta memmnuniyetleri için Visual Analog Scale (VAS) formları, yaşam kalitesinin değerlendirilmesi için de Oral Health Impact Profile-14 (OHIP-14) formları doldurtulmuştur. Bulgular: Araştırmanın istatistiksel sonuçlarına göre, olguların yaşları ve cinsiyetleri ile VAS ve OHIP skorları arasında istatistiksel olarak anlamlı bir ilişki bulunmamıştır (p>0,05). Olguların protez yaşı ile VAS konuşma skorları ile pozitif yönlü, %30,8 düzeyinde,  OHIP fonksiyonel kısıtlanma skorları ile de negatif yönlü, %32,2 düzeyinde ve istatistiksel olarak anlamlı bir ilişki bulunmuştur (p<0,05). Olguların ısırma kuvvetleri ile VAS konuşma skorları ile pozitif yönlü, %29,6 düzeyinde ve istatistiksel olarak anlamlı bir ilişki bulunmuş, OHIP skorları arasında istatistiksel olarak anlamlı bir ilişki bulunmamıştır (p>0,05).  Ayrıca erkek hastaların ısırma kuvvetleri bayanlardan istatistiksel olarak anlamlı derecede yüksek çıkmıştır (p<0,05). Sonuçlar: Tam protez kullanan hastalarda hasta memnuniyeti ve yaşam kalitesini, yaş, cinsiyet gibi demografik faktörler etkilemezken, protezleri daha eski olan ve ısırma kuvveti fazla olan hastaların konuşma yönünden daha memnun oldukları söylenebilir. Anahtar kelimeler: Hasta memnuniyeti, yaşam kalitesi, tam protez, ısırma kuvveti.